COMPARISON OF ANXIETY AND AGORAPHOBIA SCORES IN BENIGN PAROXYSMAL POSITIONAL VERTIGO BEFOREAND AFTER TREATMENT WITH EPLEY MANOEUVRE - Rani Fitria Dewi, Aldy S Rambe & Kiki M Iqbal (International Journal of Research Science and Management, 2019)
Background: Benign paroxysmal positional vertigo (BPPV) is the most vestibular disorder. Patients with BPPV often experience psychological disorders, like anxiety and panic agoraphobia. This study is aimed to evaluate the anxiety and agoraphobia scores before and after canalith repositioning manoeuvre, which is the treatment of BPPV. Methods: This is an analytic cohort study. Thirty eight samples were included in the study using consecutive sampling. Diagnosis was made with history taking, physcial examination, and Dix-Hallpike manoeuvre. The participants were asked to fill the Beck Anxiety Inventory (BAI) and Agorafobia Panic (PA) questionnaire before, after the Epley manoeuvre seven days after, and fourteen days. Results: The BAI scores before, seven days after, and fourteen days after the Epley manoeuvre were 33.97 ± 12.40, 29.42 ± 11.20, 22.97 ± 9.71, respectively. The PA scores before, seven days after, and fourteen days after the Epley manoeuvre25,92 ± 7,496, 21,24 ± 7,284, 16,05 ± 6,742, respectively. There were significant differences of BAI and PA scores before and at 7 and 14 days after Epley manoeuvre. Conclusion: The anxiety and agoraphobia panic scores were significantly decreased before and after Epley manoeuvre (day-7 and day-14).